Presidential Decree-law No. 44 of the year 2014 On Imposing a Temporary Additional Tax on The Income = قرار رئيس جمهورية مصر العربية بالقانون رقم 44 لسنة 2014 بفرض ضريبة إضافية مؤقتة على الدخل - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic